Pertukaran Sosial dalam Peran Ganda Perempuan: Studi Kasus tentang Pekerjaan Rumah Tangga dan Karier Profesional - Dimas Arsy Yanto; Halimah Nur Churil Aini; Meydina Tri Luvianasari (Lembaga Pengembangan Kinerja Dosen, 2023)
Social Exchange in Women's Dual Roles: A Case Study of Housework and Professional Career. This research investigates the dynamics of social exchange involved in women's dual roles, with a focus on the fulfillment of household work and professional career development. Social exchange theory is used as a framework to analyze how women manage their roles in an increasingly complex contemporary society. Through in-depth case studies, this research explores women's experiences in managing household responsibilities along with their efforts to achieve success in professional careers. The results of this study provide insight into the challenges and opportunities they face in carrying out their dual roles, as well as their impact on gender equality in society. The results of this research have important implications in efforts to increase gender equality and encourage more inclusive social change. This study also provides a basis for better policy thinking in supporting women in navigating their dual roles and achieving success in various aspects of their lives.